Synthesis and characterization of iron(III) oxide/polyvinyl chloride/poly(methyl methacrylate) nanocomposites. Issue 5 (2nd September 2016) - Ishaq, Muhammad; Saeed, Khalid; Ayaz, Sher; Ahmad, Imtiaz
ABSTRACT: Polyvinyl chloride/poly(methyl methacrylate) blended and iron(III) nanoparticle polyvinyl chloride/poly(methyl methacrylate) nanocomposites were prepared by solution casting. The iron(III) oxide nanoparticles were prepared using a sol-gel procedure and their particle size was less than 200 nm. Scanning electron microscopy showed that no phase separation occurred and polyvinyl chloride and poly(methyl methacrylate) were miscible. Scanning electron microscopy also showed that the iron(III) oxide nanoparticles were dispersed well within the polymer blend. Thermogravimetric analysis showed three stages for the thermal degradation for polyvinyl chloride/poly(methyl methacrylate) blend and the iron(III) oxide/polyvinyl chloride/poly(methyl methacrylate). The second degradation was possibly due to dehydrochlorination during the thermal degradation of polyvinyl chloride in the blend system. Young's modulus of the iron(III) oxide nanoparticle filled nanocomposites was from 1987.7–2471.6 MPa, which was higher than polyvinyl chloride/poly(methyl methacrylate) blend (1955.5 MPa). The stress yield (47.9–51.8 MPa) of the iron(III) oxide nanoparticle composites was higher than pure polyvinyl chloride/poly(methyl methacrylate) (47.0 MPa). The cyclic voltammograms of the pure blend and the nanocomposites were compared.